2012
DOI: 10.1515/znb-2012-0401
|View full text |Cite
|
Sign up to set email alerts
|

On the Formation and 1H NMR-spectroscopic Characterization of N,N-Diaryl-substituted Formamide Chlorides

Abstract: The reaction of N, N-diaryl-substituted formamides with oxalyl chloride gives rise, instead to the formation of the expected salt-like formamide chlorides, to the formation of corresponding non-ionic N-dichloromethyl-substituted diarylamines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…The successful synthesis of the multifunctionalized polymer ligand was confirmed by total reflection Fourier transform infrared spectroscopy (ATR-FTIR) measurements (Figure S1). Typically, the original poly maleic-anhydride shows two characteristic bands of anhydride, including a weak absorption band around 1858 cm –1 and strong band near 1773 cm –1 assigned to symmetric and asymmetric C=O stretching. , After amidation, the anhydride signal significantly decreases and three intensive amide I, II, and III bands are exhibited at around 1705, 1590, and 1236 cm –1 , respectively. , Nuclear magnetic resonance (NMR) spectroscopy was also utilized to characterize the amination reactions (Figure S2), demonstrating distinct proton signals of the carboxyl group (∼12.12 ppm), amide α-H (2.9–3.6 ppm), and phenyl ring (7.15–7.42 ppm). Figure S3 illustrates the comparison of ATR-FTIR spectra between pristine and PP-NCs. It is observed that no amide I peak is detected in the pristine NCs.…”
mentioning
confidence: 99%
“…The successful synthesis of the multifunctionalized polymer ligand was confirmed by total reflection Fourier transform infrared spectroscopy (ATR-FTIR) measurements (Figure S1). Typically, the original poly maleic-anhydride shows two characteristic bands of anhydride, including a weak absorption band around 1858 cm –1 and strong band near 1773 cm –1 assigned to symmetric and asymmetric C=O stretching. , After amidation, the anhydride signal significantly decreases and three intensive amide I, II, and III bands are exhibited at around 1705, 1590, and 1236 cm –1 , respectively. , Nuclear magnetic resonance (NMR) spectroscopy was also utilized to characterize the amination reactions (Figure S2), demonstrating distinct proton signals of the carboxyl group (∼12.12 ppm), amide α-H (2.9–3.6 ppm), and phenyl ring (7.15–7.42 ppm). Figure S3 illustrates the comparison of ATR-FTIR spectra between pristine and PP-NCs. It is observed that no amide I peak is detected in the pristine NCs.…”
mentioning
confidence: 99%